Effectiveness of food supplements in increasing fat-free tissue accretion in children with moderate acute malnutrition: A randomised 2 × 2 × 3 factorial trial in Burkina Faso. - Christian Fabiansen; Charles W Yaméogo; Ann-Sophie Iuel-Brockdorf; Bernardette Cichon; Maren J H Rytter; Anura Kurpad; Jonathan C Wells; Christian Ritz; Per Ashorn; Suzanne Filteau; André Briend; Susan Shepherd; et al. (PLoS Medicine, 2017)
Background Children with moderate acute malnutrition (MAM) are treated with lipid-based nutrient supplement (LNS) or corn-soy blend (CSB). We assessed the effectiveness of (a) matrix, i.e., LNS or CSB, (b) soy quality, i.e., soy isolate (SI) or dehulled soy (DS), and (c) percentage of total protein from dry skimmed milk, i.e., 0%, 20%, or 50%, in increasing fat-free tissue accretion. Methods and findings Between September 9, 2013, and August 29, 2014, a randomised 2 × 2 × 3 factorial trial recruited 6- to 23-month-old children with MAM in Burkina Faso. The intervention comprised 12 weeks of food supplementation providing 500 kcal/day as LNS or CSB, each containing SI or DS, and 0%, 20%, or 50% of protein from milk. Fat-free mass (FFM) was assessed by deuterium dilution technique. By dividing FFM by length squared, the primary outcome was expressed independent of length as FFM index (FFMI) accretion over 12 weeks. Other outcomes comprised recovery rate and additional anthropometric measures. Of 1,609 children, 4 died, 61 were lost to follow-up, and 119 were transferred out due to supplementation being switched to non-experimental products. No children developed allergic reaction. At inclusion, 95% were breastfed, mean (SD) weight was 6.91 kg (0.93), with 83.5% (5.5) FFM. In the whole cohort, weight increased 0.90 kg (95% CI 0.88, 0.93; p < 0.01) comprising 93.5% (95% CI 89.5, 97.3) FFM. As compared to children who received CSB, FFMI accretion was increased by 0.083 kg/m2 (95% CI 0.003, 0.163; p = 0.042) in those who received LNS. In contrast, SI did not increase FFMI compared to DS (mean difference 0.038 kg/m2; 95% CI -0.041, 0.118; p = 0.35), irrespective of matrix. Having 20% milk protein was associated with 0.097 kg/m2 (95% CI -0.002, 0.196) greater FFMI accretion than having 0% milk protein, although this difference was not significant (p = 0.055), and there was no effect of 50% milk protein (0.049 kg/m2; 95% CI -0.047, 0.146; p = 0.32). There was no effect modification by season, admission criteria, or baseline FFMI, stunting, inflammation, or breastfeeding (p > 0.05). LNS compared to CSB resulted in 128 g (95% CI 67, 190; p < 0.01) greater weight gain if both contained SI, but there was no difference between LNS and CSB if both contained DS (mean difference 22 g; 95% CI -40, 84; p = 0.49) (interaction p = 0.017). Accordingly, SI compared to DS increased weight by 89 g (95% CI 27, 150; p = 0.005) when combined with LNS, but not when combined with CSB. A limitation of this and other food supplementation trials is that it is not possible to collect reliable data on individual adherence. Conclusions Based on this study, children with MAM mainly gain fat-free tissue when rehabilitated. Nevertheless, LNS yields more fat-free tissue and higher recovery rates than CSB. Moreover, current LNSs with DS may be improved by shifting to SI. The role of milk relative to soy merits further research. Trial registration ISRCTN registry ISRCTN42569496.